Neurofilament heavy chain as a marker of neuroaxonal pathology and prognosis in acute encephalitis. (29th March 2014) - Sellner, J.; Davies, N. W.; Howard, R. S.; Petzold, A.
<x xml:space="preserve">Abstract</x> Background and purpose The neurological outcome of acute encephalitis can be devastating and early prognosis remains difficult. Biomarkers that quantify the extent of early brain injury are needed to improve the prognostic accuracy and aid patient management. Our objective was to assess whether cerebrospinal fluid (CSF) protein biomarkers of neuroaxonal and glial cell injury are elevated in distinct forms of acute encephalitis and predictive of poor outcome. Methods This was a prospective study of patients presenting with acute encephalitis to three teaching hospitals in London, UK. Levels of neurofilament heavy chain (NfH, SMI35) and S100B were quantified in CSF using enzyme‐linked immunosorbent assay. The outcome was assessed by the Glasgow Outcome Scale (GOS). Results Fifty‐six patients with acute encephalitis were recruited and classified into the following diagnostic categories: infectious (n = 20), inflammatory (n = 14) and unknown etiology (n = 22). Pathological levels of NfH and S100B were observed in 24/56 (43%) and 54/56 (96%), respectively. Patients with infectious encephalitis had significantly higher NfH levels compared with the other two groups (P < 0.05). A poor outcome (GOS < 5) was associated with significantly higher CSF NfH levels within samples taken 2 weeks after symptom onset. Conclusions This study suggests that longitudinal CSF NfH levels are of superior prognostic value compared with CSF S100B levels. Prolonged release of NfH, a marker of neuroaxonal damage, was associated with poor outcome. Potentially there is a window of opportunity for future neuroprotective treatment strategies in encephalitis.